2014
DOI: 10.1002/casp.2190
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Disclosure of Nonsuicidal Self‐injury among University Students

Abstract: Despite the widespread prevalence of nonsuicidal self-injury (NSSI) among community-based samples, little is known about which self-injurers disclose their NSSI or the factors that promote disclosure among self-injurers. To address this gap in the literature, we examined whether disclosers could be differentiated from nondisclosers on the basis of NSSI characteristics (e.g. frequency of NSSI and severity of NSSI), NSSI motivations (e.g. interpersonal and intrapersonal motivations) and psychosocial factors (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 68 publications
1
67
4
Order By: Relevance
“…This sort of challenge is common in research that relies on self-reported data. In addition, research on offline self-harm suggests that young people tend not to disclose their behaviour (Armiento, Hamza, & Willoughby, 2014). We managed these challenges by guaranteeing participants that their responses were anonymous.…”
Section: What We Didmentioning
confidence: 99%
“…This sort of challenge is common in research that relies on self-reported data. In addition, research on offline self-harm suggests that young people tend not to disclose their behaviour (Armiento, Hamza, & Willoughby, 2014). We managed these challenges by guaranteeing participants that their responses were anonymous.…”
Section: What We Didmentioning
confidence: 99%
“…NSSI has become a serious global public health concern, particularly among adolescents (Heath et al, 2008;Muehlenkamp, 2014;Muehlenkamp et al, 2012;Nock, 2010). Various studies from Asia (You and Leung, 2012), Australia (Tanner et al, 2015), Canada (Armiento et al, 2014), Europe , and the US (Sornberger et al, 2012;Brausch and Gutierrez, 2010) have found lifetime prevalence rates of NSSI among adolescent students ranges between 10-32%. Higher rates have been reported among adolescents from clinical settings ranging from 24% in Canada (Armiento et al, 2016), to 40% in Europe (Kaess et al, 2013), and 63-80% in the US (Auerbach et al, 2014;Victor et al, 2012;Weismoore and Esposito-Smythers, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, treatments developed specifically for NSSI are scarce, and access to empirically-supported treatments for this behavior is limited [ 9 ]. Online treatments carry several advantages compared to traditional face-to-face psychological treatments and may be particularly useful for treating NSSI, as this behavior is associated with high levels of shame and non-disclosure [ 23 , 24 ]. Support for the feasibility and acceptability of online ERITA was provided by findings of high levels of treatment module completion and low treatment attrition, acceptable ratings of treatment credibility, expectancy, and satisfaction (by adolescents and their parents), as well as strong ratings of therapeutic alliance.…”
Section: Discussionmentioning
confidence: 99%
“…There is also research indicating that ICBT is at least as efficacious as face-to-face CBT for a range of psychiatric disorders in adults [ 21 ]. Further, given research indicating that individuals with stigmatizing illnesses are more likely to use the Internet than traditional health care services to seek help [ 22 ], online treatment may be particularly suitable for the treatment of NSSI, given its association with shame [ 23 ] and low levels of disclosure [ 24 ]. Nonetheless, although there have been some efforts to develop web-based interventions for suicidal behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%